Exploring the feasibility of Recovery Management Checkups for Primary Care in a Federally Qualified Health Center - Dennis P. Watson; Ryan Singh; Lisa Taylor; Michael L. Dennis; Christine E. Grella; Carol Johnstone; Katherine Browne; Lisa Saldana (Frontiers Media S.A., 2024)
IntroductionPrimary care settings present an opportunity for alcohol and substance use disorder (A/SUD) screening and treatment referral. However, there are recognized deficiencies in widely used treatment referral approaches, including acute care connections, vs. those that can support longer-term recovery. Recovery Management Checkups for Primary Care (RMC-PC) is an intervention with an evidence base for improving treatment referral and subsequent recovery for primary care patients; however, the intervention has never been fully implemented outside of a research context. We conducted a feasibility study to inform a future hybrid study of RMC-PC that will test the implementation and effectiveness of the intervention in primary care practice.MethodWe used a convergent mixed method design. The study's setting was a Federally Qualified Health Center (FQHC) located in a large midwestern city. RMC-PC linkage services were administered by one of two treatment linkage managers: an FQHC linkage manager (F-LM) and a research staff linkage manager (R-LM). Quantitative data included (a) rates of positive A/SUD screening among a group of FQHC patients and (b) linkage manager service data (e.g., rate of successful meeting completion and days to completing of key events). Qualitative data included (c) an assessment of linkage manager's motivational interviewing performance and (d) a focus group with FQHC staff focused on their perspectives on RMC-PC implementation determinants. Quantitative data were summarized using descriptive statistics, and linkage manager performance was compared. Qualitative data were analyzed using a hybrid deductive-inductive process.ResultsFifty percent of patients screened met moderate-high A/SUD risk. Eleven of 16 recruited patients completed at least one linkage manager meeting, with 63% completing both meetings. The F-LM delivered RMC-PC services alongside other duties successfully; however, three primary barriers to FQHC implementation were identified (difficulties applying motivational interviewing, incompatibilities of screening with FQHC technology and workflow, and lack of billing mechanism to support services).ConclusionRMC-PC is feasible for FQHC staff to deliver, though issues identified must be considered to ensure successful and sustainable implementation. Knowledge gained will inform a packaged implementation strategy that will be used in a future hybrid trial.